2016
DOI: 10.1080/19393210.2016.1213318
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol, zearalenone and T-2 in grain based swine feed in Hungary

Abstract: Fusarium genera can produce trichothecenes like deoxynivalenol (DON), zearalenone (ZEN) and T-2 toxin, which can occur in feed cereal grains. Enzyme-linked immunosorbent assays (ELISA) tests of different Hungarian swine feedstuff proved that these mycotoxins were present. In this survey, 45 feed samples from 3 significant Hungarian swine feedstuff manufacturers were tested. ELISA methodology validation showed mean recovery rates in ranges from 85.3% to 98.1%, with intermediate precision of 86.9-96.9% and varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…These studies have described numerous adverse effects of mycotoxin on human and animal health. similar to the results of the present study (Tima et al, 2016). In 2018,…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These studies have described numerous adverse effects of mycotoxin on human and animal health. similar to the results of the present study (Tima et al, 2016). In 2018,…”
Section: Resultssupporting
confidence: 93%
“…These studies have described numerous adverse effects of mycotoxin on human and animal health. Tima et al surveyed 45 feed samples from three major Hungarian swine feedstuff manufacturers and detected ZEA in all tested samples, similar to the results of the present study (Tima et al, 2016). In 2018, Hassan et al detected mycotoxins in cereals used as animal feed in a Qatari market; OTA was detected in 44% of mixed cereals, 40% of corn samples, and 60% of wheat and wheat bran samples.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Deoxynivalenol is one of the most abundant Fusarium mycotoxins. In the last two decades, several studies indicated DON contamination in harvested cereals and animal feeds (Tima et al 2016a, b) and revealed exposures above the tolerable daily intake (TDI: 1μg/ bw kg) to DON in the German and Austrian populations (Warth et al 2012; Gerding et al 2014) where the provisional daily intake (PDI) exceeded the TDI in 12% or 33% of the volunteers, respectively. As some effects triggered by DON can occur in vivo in the brain at concentrations close to the TDI (Maresca 2013), neurological damage is a risk.…”
Section: Discussionmentioning
confidence: 99%
“…T-2 toxin (T-2) is one of the most toxic fungal toxins and is the most common cause of poisoning in humans and animals resulting from the consumption of contaminated cereal food and feed ( Tima et al., 2016 ; Van Der Fels-Klerx et al., 2012 ). The food and feedstuff most frequently contaminated with T-2 include wheat, maize, barley, oats and rye, along with their processed products, which results in huge economic losses ( Tutelyan et al., 2013 ; Zakharova et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%